Insights Into the Mechanisms of Phreatic Eruptions From Continuous High Frequency Volcanic Gas Monitoring: Rincón de la Vieja Volcano, Costa Rica - Battaglia, Angelo; de Moor, J. Maarten; Aiuppa, Alessandro; Avard, Geoffroy; Bakkar, Henriette; Bitetto, Marcello; Mora Fernández, M. M.; Kelly, Peter; Giudice, Gaetano; Delle Donne, Dario; Villalobos, Hairo (Frontiers in Earth Science, 2019)
Understanding the trigger mechanisms of phreatic eruptions is key to mitigating the effects of these hazardous but poorly forecastable volcanic events. It has recently been established that high-rate volcanic gas observations are potentially very suitable to identifying the source processes driving phreatic eruptions, and to eventually detecting precursory changes prior to individual phreatic blasts. In February-May 2017, we deployed a Multi-GAS instrument to continuously monitor gas concentrations in the crater lake plume of Rincón de la Vieja, a remote and poorly monitored active volcano in Costa Rica, site of frequent phreatic/phreatomagmatic eruptions. Forty-two phreatic/phreatomagmatic eruptions were seismically recorded during our investigated period, 9 of which were also recorded for gas by the Multi-GAS. To the best of our knowledge, these represent the first instrumentally measured gas compositions during individual phreatic/phreatomagmatic explosions at an active volcano. Our results show that during background quiescent degassing the Rincón de la Vieja crater lake plume was characterized by high CO2/SO2 ratios of 64 ± 59 and H2S/SO2 ratios of 0.57 ± 0.20. This composition is interpreted as reflecting hydrothermal (re)processing of magma-sourced gas in the sub-limnic environment. Phreatic blasts were recorded by the Multi-GAS as brief (1–2 min long) pulses of elevated gas mixing ratios (up to 52 ppmv SO2 and >3,000 ppmv CO2), or more than an order of magnitude higher than during background degassing ( 1 ppmv SO2 and 450 ppmv CO2). During the phreatic eruption(s), the H2S/SO2 ratio was systematically lower (<0.18) than during background degassing, but the CO2/SO2 ratio remained high (and variable), ranging from 37 to 390. These S-poor compositions for the eruptive gas imply extensive processing of the source magmatic gas during pre-eruptive hydrothermal storage, likely by deposition of native S and/or sulfate. Our gas results are thus overall consistent with a mechanism of phreatic eruptions triggered by accumulation of magmatic-hydrothermal gases beneath a hydrothermal seal. We claim that real-time Multi-GAS monitoring is urgently needed at other crater lake-hosting volcanoes (e.g., Ruapehu, Aso), where phreatic eruptions may similarly be preceded by phases of reduced S degassing at the surface.